Exact Number of Positive Solutions for a Class of Two-Point Boundary Value Problems - Yanmin Niu; Baoqiang Yan (Journal of Applied Mathematics)
This paper considers the existence of positive solutions of the boundary value problems and , where and is a positive parameter. Using a time-map approach, we obtain the exact number of positive solutions in different cases.